L’impatto dei ritiri estivi delle squadre di calcio in Trentino-Alto Adige tra vantaggi oggettivi e prospettive - Castellano, Simona (Eracle. Journal of Sport and Social Sciences, 2019)
The Italian region Trentino-Alto Adige has drawn vital energy from football, becoming an exceptional tourist destination for summer holidays in the Alps, thanks to the pre-season summer training camps of several football teams. Starting from the assumption that the sense of belonging push football fans to follow their team during the preseason and starting from the point that the presence of the tourists led to improvements of these areas, what is still possible to do to improve the involvement of tourists on these sites? This paper will try to analyze new ways of interacting and involving tourists, that are now also “networked publics” and always on users. The widespread of a social network like Instagram, combined with the passion for sports, can increase a new grassroots promotion mode, that leads users, with their own storytelling, to become the spokesperson of a territorial promotion that starts from the bottom.